أثر نظام تخطيط موارد المؤسسة على أداء المؤسسة الإقتصادية -دراسة حالة المديرية الجهوية الوطنية لشركة سونطراك السطح(عين أميناس) - محمد لعبيدي عبيدي; ضاوية طليبة; سعد لكحل (university of eloued جامعة الوادي, 2024)
"هدفت هذه الدراسة إلى التعرف على أثر نظام تخطيط موارد المؤسسة على أداء المؤسسة الاقتصادية، من خلال دراسة ميدانية بفرع شركة سوناطراك بولاية عين أميناس. كما تم تناول المفاهيم المتعلقة بنظام تخطيط موارد المؤسسة والمفاهيم الأساسية المتعلقة بالأداء في المؤسسة الاقتصادية. الجانب التطبيقي لدراسة ميدانية بالمديرية الجهوية الوطنية لسوناطراك STAH لعينة تصل إلى 80 شخصا. ولتحقيق هذا الهدف اعتمدنا على المنهج الوصفي التحليلي وأسلوب الاستبيان كأداة للدراسة وجمع المعلومات. ولتحليل الاستبيان اعتمدنا على التحليل الإحصائي الوصفي باستخدام برنامج SPSS.‏ توصلت الدراسة الميدانية إلى وجود تأثير لإدارة الموارد البشرية، والإدارة المالية، وإدارة سلسلة التوريد على أداء المنظمة في عينة من مديرية STAH الإقليمية، ولا يوجد تأثير على إدارة المخزون." This study aimed to identify the impact of the enterprise resource planning system on the performance of the economic enterprise, through a field study in a branch of the Sonatrach company in the state of In Amenas. Concepts related to the enterprise resource planning system and basic concepts related to performance in the economic enterprise were also addressed. The applied aspect of a field study in the National Regional Directorate of Sonatrach STAH for a sample of up to 80 people . To reach this goal, we relied on the descriptive analytical approach and the questionnaire method as a tool for studying and collecting information. To analyze the questionnaire, we relied on descriptive statistical analysis using the SPSS program . The field study found that there is an impact of human resources management, financial management, and supply chain management on the organization’s performance in a sample of the STAH regional directorate, and there is no impact on inventory management.
Keywords: نظام تخطيط موارد المؤسسة، الأداء، نظم المعلومات، المؤسسة الإقتصادية enterprise resource planning system; performance; information systems; economic enterprise.